Current strategies for managing chronic thromboembolic pulmonary hypertension: results of the worldwide prospective CTEPH Registry - YILDIZELİ, BEDRETTİN (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2021)
Background Pulmonary endarterectomy (PEA), pulmonary arterial hypertension (PAH) therapy and balloon pulmonary angioplasty (BPA) are currently accepted therapies for chronic thromboembolic pulmonary hypertension (CTEPH). This international CTEPH Registry identifies clinical characteristics of patients, diagnostic algorithms and treatment decisions in a global context. Methods 1010 newly diagnosed consecutive patients were included in the registry between February 2015 and September 2016. Diagnosis was confirmed by right heart catheterisation, ventilation-perfusion lung scan, computerised pulmonary angiography and/or invasive pulmonary angiography after at least 3 months on anticoagulation. Results Overall, 649 patients (64.3%) were considered for PEA, 193 (19.1%) for BPA, 20 (2.0%) for both PEA and BPA, and 148 (14.7%) for PAH therapy only. Reasons for PEA inoperability were technical inaccessibility (n=235), comorbidities (n=63) and patient refusal (n=44). In Europe and America and other countries (AAO), 72% of patients were deemed suitable for PEA, whereas in Japan, 70% of patients were offered BPA as first choice. Sex was evenly balanced, except in Japan where 75% of patients were female. A history of acute pulmonary embolism was reported for 65.6% of patients. At least one PAH therapy was initiated in 35.8% of patients (26.2% of PEA candidates, 54.5% of BPA candidates and 54.1% of those not eligible for either PEA or BPA). At the time of analysis, 39 patients (3.9%) had died of pulmonary hypertension-related causes (3.5% after PEA and 1.8% after BPA). Conclusions The registry revealed noticeable differences in patient characteristics (rates of pulmonary embolism and sex) and therapeutic approaches in Japan compared with Europe and AAO.
Keywords: ANGIOPLASTY; ENDARTERECTOMY; HEMODYNAMICS; RIOCIGUAT; RISK